Penerapan Konsep Limit Fungsi dalam Kehidupan Sehari-Hari: Dari Kecepatan hingga Ekonomi - Sukendar, Bariq Hibatullah; Jessie Irvine; Saputri, Sinta Dwi; Hernaeny, Ul’fah (Jurnal Studi Multidisiplin Qomaruna, 2025)
The concept of limits in functions is a fundamental aspect of calculus with various practical applications in everyday life. This study investigates the application of limits in the fields of physics, economics, and biology. In physics, the concept of limits is used to calculate instantaneous velocity and acceleration, which are crucial for understanding the dynamics of motion. In the economic sector, limits play a role in marginal cost analysis and predicting economic growth, while in biology, limits are employed to model population growth approaching the carrying capacity of the environment. Furthermore, this study identifies gaps in the teaching of limits in schools and universities, particularly in the integration of interdisciplinary applications. The findings of this research indicate that limits are not only mathematical analysis tools but also practical solutions to various challenges across different fields of life.